2012
DOI: 10.1111/j.1939-3938.2011.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual assault nurse examiners’ perceptions of funding challenges faced by SANE programs: “It stinks”

Abstract: Even though Sexual Assault Nurse Examiner (SANE) programs began over 30 years ago, and there is currently greater awareness of sexual violence, the question regarding the financial security of SANE prgrams remains a contemporary concern. Data from interviews with 40 SANEs', many of whom were also directors, from programs located in four states indicated that lack of funding continues to present challenges. Most (72%) directors revealed that there are problems with funding. Directors voiced concerns about progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Building a SANE program and strengthening its support infrastructure needs to be built on an understanding of possible local solutions to considerable challenges that ensure the overall success of the SANEs. We found that the existing barriers to SANEs in our target population are similar to those described in the literature (Campbell et al, 2007;Maier, 2012;Nielson et al, 2015;Shefali & Lai, 2013).…”
Section: ▪ Conclusionsupporting
confidence: 83%
“…Building a SANE program and strengthening its support infrastructure needs to be built on an understanding of possible local solutions to considerable challenges that ensure the overall success of the SANEs. We found that the existing barriers to SANEs in our target population are similar to those described in the literature (Campbell et al, 2007;Maier, 2012;Nielson et al, 2015;Shefali & Lai, 2013).…”
Section: ▪ Conclusionsupporting
confidence: 83%
“…Before the RUSANE program, Hendry County had zero certified or trained SANE nurses. Meeting this need has allowed these nurses to have IAFN didactic and clinical training that is not only evidence based but also learner centered and reduces traveling and financial stress (Maier, 2012). Ensuring that our curriculum was IAFN accredited, including our clinical requirements, provided our trainees and clinical partners with confidence that they were receiving proper training and support.…”
Section: Discussionmentioning
confidence: 99%
“…SANE programs need inexpensive and effective options for patient follow-up that can document communications that may constitute medical record data. Many SANE programs face sustainability challenges (Maier, 2012). A costly intervention such as Text-SAFE that was implemented using a text-messaging company would be prohibitive for most SANE programs.…”
Section: Discussionmentioning
confidence: 99%